Are We Different? Evaluating Cultural Values of Local Ethnic Groups in Sarawak, Malaysia - Ellin, Ng; Norazirah, Ayob (Common Ground Research Networks, 2023)
Although multiethnic groups form the national culture of Malaysia, they are still very different from one another in terms of their cultural values. This study aimed to examine the cultural values of five major local ethnic groups working in the budget hotel sector in Sarawak, Malaysia. It also investigated the differences in the cultural values among the five local ethnic groups. In an empirical survey, the Cultural Values Scale was administered to 119 employees throughout Sarawak. Data were analyzed using descriptive statistics, and the Mann-Whitney U test was used to assess the differences in cultural values. The findings revealed that all ethnic groups scored high in all cultural dimensions. However, there were significant differences in the cultural values among the five ethnic groups. The results and discussion have been included in this study. This study is noteworthy for researchers exploring the cultural values of the minor ethnicities in Sarawak and Malaysia.